AB0368 AC-Cute: An Open-Label Study To Evaluate Non-Progression of Structural Joint Damage in Patients with Moderate To Severe Active Rheumatoid Arthritis Treated with Subcutaneous Tocilizumab. (15th July 2016) - Bird, P.; Peterfy, C.; DiCarlo, J.; Joshua, F.; Hall, S.; Griffiths, H.; Youssef, P.; Barrett, R.; Button, P.
Abstract : Background: Clinical efficacy of subcutaneous tocilizumab (SC-TCZ) has been demonstrated in rheumatoid arthritis (RA); however the effect of SC-TCZ on joint damage has not yet been assessed. AC-CUTE (NCT01951170 ) aimed to evaluate the effects of weekly SC-TCZ on structural change in patients (pts) with moderate-severe active RA, who were inadequate responders to MTX/MTX-intolerant or inadequate responders to a single anti-TNF. Objectives: To assess radiographic and MRI progression at week 24, in pts receiving SC-TCZ as monotherapy or in combination with MTX and/or conventional (c) DMARDs. Methods: An open-label, multi-centre, prospective, single-arm study. Pts received TCZ 162mg weekly, single fixed dose SC injection, monotherapy or in combination with MTX or other cDMARDs. Primary endpoint was absolute change in radiographic Genant-modified Sharp Score (mTSS) between screening and week-24. Secondary endpoints were absolute change from baseline in RAMRIS of MRI erosions, synovitis and osteitis, and MRI cartilage loss (CARLOS). Efficacy parameters included change from baseline (initiation of SC-TCZ) in mTSS, DAS28, CDAI, SDAI and ACR20/50/70. The full analysis set population included pts who received at least 1 dose SC-TCZ, and was used for reporting safety, tolerability and efficacy. Subgroup analyses were split into SC-TCZ monotherapy [SC-TCZM: SC-TCZ monotherapy or SC-TCZ+cDMARDs other than MTX] and SC-TCZ in combination [SC-TCZC: SC-TCZ+cDMARDs including all MTX regimens]. Results: 52 pts enrolled from 10 Australian sites; majority females (79%), median age 59 yrs (min 28, max 79) and 5 yrs (min 0, max 31) median duration of RA. Pts in SC-TCZM had longer disease duration at baseline and higher mTSS score. 29 pts completed 24 weeks of treatment. Mean change from baseline for erosion/JSN/mTSS was 0.162/0.485/0.647 in SC-TCZM and 0.124/0.238/0.362 in SC-TCZC respectively; changes relative to baseline and between subgroups were not significant (p>0.05). Mean changes from baseline in MRI erosion/cartilage loss/synovitis/osteitis were 0.794/0.0882/-1.56/-2.88 for SC-TCZM and 0.955/0.1439/-1.68/-3.77 for SC-TCZC. Change from baseline for each MRI measure within SC-TCZC was significant (p<0.05); however no significant differences were observed between the 2 subgroups (p>0.1). At 24 weeks, decrease in DAS28 from baseline was significant for both subgroups (p=0.004 for SC-TCZC; p<0.0001 for SC-TCZM); however no significance was observed between subgroups (p=0.3). The proportion of pts achieving DAS28 remission (<2.6) over 24 weeks ranged from 65% for SC-TCZC to 89% for SC-TCZM. 3 pts reported serious adverse events, asthma, anaemia and Weber B Ankle Fracture; deemed unrelated to study medication. Conclusions: There was no significant radiographic progression during the study period across groups. Mean changes in MRI variables were not significant in SC-TZM. MRI changes in SC-TCZC were significant for joint damage progression, as well as regression of synovitis and osteitis. Acknowledgement: Sponsored by Roche Products, Pty. Ltd. Medical writing provided by Joseline Ojaimi from Roche. Disclosure of Interest: P. Bird: None declared, C. Peterfy Consultant for: Roche Products, Pty. Ltd, J. DiCarlo Consultant for: Roche Products, Pty. Ltd, F. Joshua: None declared, S. Hall: None declared, H. Griffiths: None declared, P. Youssef: None declared, R. Barrett Employee of: Roche Products, Pty. Ltd, P. Button Employee of: Roche Products, Pty. Ltd